PENGARUH PENGGUNAAN MEDIA LOOSE PARTS TERHADAP KECERDASAN LOGIKA MATEMATIKA PADA ANAK USIA 5-6 TAHUN DI RA AL-HIDAYAH KEC MEDAN SELAYANG T.A 2023-2024 - Khoirunnisa Khoirunnisa; Aminda Tri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The objective of this research is to determine the effect of using loose parts media of mathematical logic intelligences in children aged 5-6 years in RA Al-Hidayah District Medang Selayang School year 2023-2024. The type of sample selection used by researchers is using a Non-Probability sampling sample type, namely saturated sampling. The type off research used a quantitative method with a one-group pretest-posttest desaign using loose parts media. The research intruments and data collection techniques used were observation and documentation sheets. Based on the results of data analysis in the normality test using one sample kolmogorov-smirnov, the sig. Sirnov test > alpha level = 0,05, while the data obtained is 0.054 > 0.05. based on the results of the hypothesis, The Tcount value = 1.906 > 1.721 and because dk = (n-1) = 21 and the real level of alpha = 0.05 so it can be conccluded that the value of T.count > T.Table, thus hypothesis H0 is rejected and H1 is accepted. So it can be stated that there is a significant influence of the use of loose parts media on mathematical logic intelligences in children aged 5-6 years in RA Al-Hidayah District. Medan Selayang school year 2023-2024.